Pola dan Teknis Baru Pendistribusian Zakat di Indonesia - Cholidi Cholidi; Zuraidah Zuraidah (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
The provision of zakat aims to improve the economic condition of mustahik (zakat recipient) and overcome some of the problems they face. From year to year, there is an increase in the amount of zakat received by the institutions that manage it. However, up to now there are still many mustahik who are still living under a decent and adequate line. This shows that the role of zakat in improving the economic condition of mustahik is not yet very visible. Or in other words the performance of zakat is not yet maximal in controlling poverty. It is more ironic that disasters sometimes occur in the zakat distribution area. This event implies that there is a mistake in the management of zakat, especially in the field of distribution. Is there a mistake in distributing zakat in Indonesia? Therefore, the question arises: Is there no clue from the Qur'an and or hadith about the pattern and technical distribution of zakat? This research will found the pattern and technical conclusions in: (1) Zakat pick-up (2) Do not move zakat (3) Circles (spirals) like conch shells.